2018
DOI: 10.1177/1357633x18765059
|View full text |Cite
|
Sign up to set email alerts
|

Parent perspectives of neonatal tele-homecare: A qualitative study

Abstract: Introduction Neonatal homecare for preterm infants is a method of supporting families and monitoring infant growth in the home setting. Telehealth may be used to deliver specialist neonatal care remotely, using online communication methods. This study explored parental experiences with neonatal tele-homecare (NTH). Methods Semi-structured interviews were conducted with 49 parents whose preterm infants had received NTH from a neonatal intensive care unit (NICU) in Denmark. Interview transcripts were analysed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 42 publications
(72 reference statements)
4
59
0
Order By: Relevance
“…Another important finding was the significance of having easy access to communication with nurses through video consultation. This finding is similar to that of Holm et al [14]. However, unlike Holm et al [14], we found that an important factor for the parents was that the video consultations saved time that could be spent as important quality time with the infant, as the video consultations did not require time for transportation.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Another important finding was the significance of having easy access to communication with nurses through video consultation. This finding is similar to that of Holm et al [14]. However, unlike Holm et al [14], we found that an important factor for the parents was that the video consultations saved time that could be spent as important quality time with the infant, as the video consultations did not require time for transportation.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to that of Holm et al [14]. However, unlike Holm et al [14], we found that an important factor for the parents was that the video consultations saved time that could be spent as important quality time with the infant, as the video consultations did not require time for transportation. This finding is line with Lindberg [23], who found that video consultations were especially important when families lived a long distance from the hospital.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations